IMMORTAL HUMAN: TINDAKAN MANUSIA UNTUK ABADI DALAM PANDANGAN MUHAMMAD IQBAL - Imam Bustomi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2021)
This study aims to find the concept of immortality in Iqbal's view by making it relevant to human action in the world. Human action that leads to morality is needed to provide awareness that human perfection can only be achieved by maximizing actions in accordance with the enhancement of his self-concept. To achieve this goal, this study uses qualitative methods with the type of literature study. As an analysis tool, this study uses content analysis techniques. Based on the data generated, this study found that conscious and free human action is the key for humans to achieve perfection. The resulting perfection can lead humans to immortality by absorbing the surrounding reality, including the absorption of the great ego of the Most Perfect. The offer of perfection given by Iqbal reconstructs the concept of timelessness in the views of classical Islamic thinkers that lead to life after death. Eternal in Iqbal's view does not refer to a place but to a state so that Heaven and Hell which are considered places of eternity are conditions related to the process of human attainment towards immortality.